Computational analysis of β cell Ca2+ dynamics in situ - Yong, Fiona Su Wern (Nanyang Technological University, 2024)
β hubs are a distinct subpopulation of pancreatic β cells arising from intra-islet β cell heterogeneity. Subject to the challenges of data collection in vivo in the living animal after engraftment of islets into the anterior eye chamber, mouse β hubs seem to be in a transient state when it comes to retaining their identity as hubs over time, with healthy islets alternately recruiting more hubs and losing other hubs over a 2-week period. Factors governing the state of β hubs remain ill-defined although recently some studies have identified contributory mechanisms. A major challenge lies in interpreting the islet cell imaging data that serves as a proxy for functionality. Here, development and refinement of the signal binarisation method of connectivity analysis has proven to be invaluable in understanding the acquired image data. Using this signal binarisation connectivity analysis, mitofusins MFN1 and MFN2 seem to be necessary for maintaining β cell-β cell connectivity, with their deletion resulting in fewer hub connections compared to controls. By the same analysis methodology, the protein coding gene Nnat also appears to play a role in β cells heterogeneity, with a lower proportion of hub cells in the Nnat+ population, suggesting that Nnat might contribute to β cell heterogeneity through differential DNA methylation. However, result interpretation based on 2D imaging is a major drawback. Differences in results based on 2D and 3D imaging of the same islet highlights the importance of using 3D imaging for more comprehensive connectivity analyses, a novel finding that calls for caution in interpreting results obtained from a single focal plane.